The Metabolite Profile in Culture Supernatant of Aster yomena Callus and Its Anti-Photoaging Effect in Skin Cells Exposed to UVB - Woo Sik Kim; Jeong Hun Seo; Jae-In Lee; Eun-Sil Ko; Sang-Min Cho; Jea-Ran Kang; Jong-Hoon Jeong; Yu Jeong Jeong; Cha Young Kim; Jeong-Dan Cha; Young-Bae Ryu (Plants, 2021)
Aster yomena (A. yomena) extract has anti-inflammatory, antioxidant, anti-asthma, and anti-atopic effects. However, the commercial use of A. yomena extract requires a long processing time with specific processing steps (including heat treatment and ethanol precipitation), and there are various environmental problems. We aimed to build a system to produce A. yomena extract by culturing the callus in a bioreactor that can allow rapid process scale-up to test the effect of extract (AYC-CS-E) isolated from culture supernatant of A. yomena callus on photoaging of human keratinocytes (HaCaT) caused by ultraviolet B (UVB) exposure. Through screening analysis based on ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC/Q-TOF-MS), 17 major metabolites were tentatively identified from AYC-CS-E for the first time. The suppression of cell proliferation caused by UVB was effectively alleviated in UVB-irradiated HaCaT cells treated with AYC-CS-E. Treatment with AYC-CS-E strongly induced the formation of type I procollagen and the inhibition of elastase in UVB-irradiated HaCaT cells and significantly reduced the expression of matrix metalloproteinase (MMP)-1. In addition, treatment of UVB-irradiated HaCaT cells with AYC-CS-E effectively improved various factors associated with an inflammatory reaction, skin damage recovery, skin moisture retention, and hyper-keratinization caused by photoaging, such as reactive oxygen species (ROS), pro-inflammatory cytokines, transforming growth factor beta (TGF-β), MMP-3, MMP-9, filaggrin, hyaluronic acid synthase 2 (HAS-2), keratin 1 (KRT-1), nuclear factor-kappa B (NF-κB), and nuclear factor erythroid 2-related factor 2 (Nrf2) at the gene and protein levels. These results suggest that AYC-CS-E can be used as a cosmetic ingredient for various skin diseases caused by photoaging, and the current callus culture system can be used commercially to supply cosmetic ingredients.